UJI EFEKTIVITAS EKSTRAK ETANOL BUAH BINTARO (Cerbera odollam Gaerthn) TERHADAP PENURUNAN GLUKOSA DARAH PADA TIKUS PUTIH (Rattus norvegicus) - Masri, Anshari; duppa, muhammad taufiq; Rukman, Wira Yustika; Syafruddin; Sitti Nurjannah; Delvi Sara JIhan; Ermawati; dupppa, muhammad taufiq (Akademi Farmasi Yamasi Makassar, 2025)
This study aims to determine the efectivity of Bintaro Fruit (Cerbera odollam gaerthn) Ethanol Extract Against Blood Glucose Decrease in White Rats (Rattus Norvegicus. The research design used was an experimental laboratory carried out in the pharmacology laboratory of the Department of Pharmacy, Pancasakti University. This study used 15 rats. male white rats were divided into 5 groups consisting of group I as a negative control by giving 1% w/v Na.CMC suspension, groups II, III, IV as a treatment group given Bintaro Fruit extract 1% w/v, 3% w/v, 5% w/v And group V was given Glibenclamide suspension as a positive control.The results showed that the percentage reduction in blood glucose for negative control, treatment and positive groups was 11.37%, 32.03%, 65, respectively. 46%, 86.15%, 95.5% The most effective concentration was 5% w/v concentration with an average value of 86.15% reduction, but it has not been able to match the effectiveness of Glibenclamide. in statistical testing using the Graphad Prims program for an alpha rate of 0.05, P value of 0.0001 is significant, the F value is 608.3.